Pesantren And Community Economy : (Study Of The Effectiveness Of Micro Waqf Bank (BWM) Pesantren In Sumenep) - Zaid Raya Argantara (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2023)
The existence of pesantren is required to respond to social phenomena that occur from time to time, pesantren play the first role in social change, especially in its three main objectives, namely; (1) As an institution in the development of ulama (2), as a form of resilient Human Resources (HR), and (3), as a community development institution. BPS data states that Sumenep City is ranked in the top three with poor populations in East Java. One of the community empowerment institutions at this time is the Islamic micro waqf bank (BWM) managed by pesantren. This research measures the level of effectiveness of community empowerment through Islamic micro waqf banks managed by pesantren in the city ofumenep. This study uses descriptive qualitative methods with data collection sources through interviews, observation and documentation, descriptive qualitative approaches are used in this study to determine the effectiveness of Islamic micro waqf banks (BWM) managed by pesantren. The population in this research is BWM located in the city ofumenep, namely in BWM Al-Pend Barokah Mandiri and BWM Kariman Birajuda Al-Karimiyah. The efforts of sharia microfinance institutions (BWM) Al-Pend Barokah Mandiri and BWM Kariman Birajuda Al-Karimiyah in conducting community economic empowerment are by providing financing without collateral and interest, and providing routine assistance every week. The effectiveness level of BWM Al-Pend Barokah Mandiri and BWM Kariman Birajuda Al-Karimiyah is at a percentage level of 87%, this rating explains that BWM Al-Pend Barokah Mandiri and BWM Kariman Birajuda Al-Karimiyah Islamic boarding schools are currently included in the moderately effective category.